Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. F. Montseny, in costume, standing in the middle
Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. F. Montseny, in costume, standing in the middle.